Promoting Competitiveness by Fighting Against Abuses of a Dominant Market Position - Lucia Irinescu (CES Working Papers, 2015)
Competition is a basic mechanism of the market economy involving supply and demand. The legislative framework of the European competition policy is provided by the Treaty on the Functioning of the European Union (TFEU)(Articles 101–109). Without an effective EU competition policy, the Single Market cannot reach its full potential. Competition policy is also crucial in allowing the EU to crack down on abuses of dominant position, cartels and concerted practices that harm consumers. To be in a dominant position is not itself illegal. A dominant company has a special responsibility to ensure that its conduct does not distort competition.
Keywords: K21; L40; L44; 330; competition; anti-competitive practices; antitrust policy